PUTUS SEKOLAH POTRET BURAM PENDIDIRAN RITA - Unifah Rosyidi; W.M. Rachmawan (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2005)
School drop-out, illiteracy and genderequariumaresomeoftheseriousproblems faced by developingcountries,Inclonesiais no eurption. In1984, Indonesia dea'ared a state sanctioned movement of six-year basic education, followed by a similar movement of nine obligatory education which should have been thoroughly completed in 2004. It seemed that due to economic crisis, this program had to be stretched out to the especially o(terIndonesia has given its commitment to Dakar accord on Education for All The logical consequence ofthis accond is that by theyear 2015 Indonesia should befreefivm illiteracy and by theyear 2008 the program ofnineyear obligatory education should be completely realized This is a deicult test on the government's commitment in this case This artide is an attempt to describea common phenomenon ofschool-drop-out alangwith the exposure ofthe root ofthe problem, the alternative solution, the constraints, and the critical notes. The key to theproblem is the seriuousness on thepart ofthe governmentand schools as well as the awareness ofthe sodety.